Enhancing the Performance of DFIG Wind Turbines Considering Excitation Parameters of the Insulated Gate Bipolar Transistors and a New PLL Scheme - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
The major aim of successful synchronization of a wind turbine system to the grid, is to mitigate electrical and mechanical stresses on the wind generator. During transient, the gearbox, shaft and rotor of the wind generator could be damaged due to mechanical stress. Also, the rotor and stator windings of the wind generator, including its insulation could be affected. In this paper, an extensive analysis of the effects of the excitation parameters of the power converter Insulated Gate Bipolar Transistors (IGBTs), on the transient performance of the Doubly Fed Induction Generator (DFIG) was carried out considering different scenarios. The salient part of this work is that, the best excitation parameters of the IGBTs were used for further analysis of the wind generator, considering a new Phase-Locked-Loop (PLL) scheme. The PLL computes phase displacement of the grid required to achieve orientation and synchronization control. Consequently, it helps in preventing power system distortion due to stator-grid interphase. This paper proposes a new PLL control strategy and Series Dynamic Braking Resistor (SDBR) combined approach, to augment the fault ride through capability of a variable speed wind turbine DFIG-based. The SDBR helps in the post fault recovery of the wind generator. Simulations were run in Power System Computer Aided Design and Electromagnetic Transient Including DC (PSCAD/EMTDC) for severe fault conditions, to test the robustness of the controllers employed. The results show that the proposed hybrid control strategy help in the fast recovery of the DFIG wind generator variables, during fault conditions.